GeO2 Doped Optical Fiber Plasmonic Sensor for Refractive Index Detection - Gangwar, Rahul Kumar; Min, Rui; Kumar, Santosh; Li, Xiaoli (Frontiers in Physics, 2021)
In this article, a D-shaped optical fiber refractive index (RI) sensor based on surface plasmon resonance effect is demonstrated. The gold film is placed at the flat portion of the optical fiber along with the sensing analytes of the different RIs to excite the plasmonic interactions. Sensing properties are investigated by using the finite element method. The maximum sensitivity of the proposed sensor is achieved as high as 20863.20 nm/RIU with the maximum resolution of 4.79×10-6 RIU and figure of merit of 308.38 RIU-1 for an analyte with RI 1.43 by optimizing the different parameters of the sensor with maximum phase matching between the core mode and surface plasmon mode. The high sensitivity of the sensor offers a promising approach for the detection of unknown RI analyte in chemical and biological fields in the near-infrared region.